Pendampingan Pencatatan dan Penyusunan Laporan Pertanggungjawaban Keuangan Berbasis Tri Hita Karana Pada Subak Saradan Desa Adat Sibanggede, Badung - Ida Ayu Putu Widani Sugianingrat; Cokorda Gde Bayu Putra; Putu Etika Wulandari; I Gede Ariasa; I Dewa Gede Adi Ambara Yoga (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The traditional subak irrigation system is a driving force in achieving farmer welfare, this system is inherited from generation to generation as the wisdom of the local Hindu community in Bali by adhering to the Tri Hita Karana concept in it. This study aims to determine how a well-organized financial recording system can produce quality and accountable reports. This study was carried out by implementing three stages, namely: 1. Socialization, 2. Observation, 3. Assistance in recording and compiling accountability reports. To realize this, assistance in recording and compiling financial accountability reports was carried out as a basic means in managing financial reports. The object of this study was the administrators and members of the subak in the Sibanggede Traditional Village. The results of this study indicate that one of the subaks in the Sibanggede Traditional Village, namely Subak Saradan, still carries out recording manually so that the recording and compilation of subak financial accountability reports have not been carried out optimally and are accountable to subak members.